The Role Of Sustainable School Culture Implementation On Commitment and Performance of School Employees - Mohzana (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
The purpose of this study is to analyze the relationship between the variable sustainable school culture implementation and commitment, the relationship between the variable sustainable school culture implementation and the performance of school employees and the relationship between the variable commitment and the performance of school employees. social media to respondents. The respondents of this study were 360 school teachers who were determined by simple random sampling. The questionnaire was designed using a Likert scale of 1 to 7. Analysis of the research data used structural equation modeling (SEM) with SmartPLS 3.0 software tools. The stages of data processing in this study were validity testing, reliability testing and hypothesis testing. The independent variables of this study were sustainable School culture and commitment; and the dependent variable is school employee performance. The results of this study are that the variable sustainable school culture implementation has a positive and significant effect on commitment, the variable sustainable school culture implementation has a positive and significant effect on the performance of school employees and the commitment variable has a positive and significant effect on commitment to the performance of school employees.